CORRELATION BETWEEN SURFACE AREA AND ATTERBERG LIMITS OF FINE-GRAINED SOILS - Dolinar B.; Mišič M.; Trauner L. (My University, 2007)
As the water content is increased, the consistency of a fine-grained soil changes from a semi-solid state to a plastic state and finally to a liquid state. The plastic limit (PL) is the point at which the consistency, caused by the soil water content, is transformed from a semi-solid state to a plastic state. The liquid limit (LL) is the point at which the consistency is transformed from a plastic state to a liquid state. The plastic limit and liquid limit are often collectively referred to as the Atterberg (or consistency) Limits. Although the liquid and plastic limits are easily determined, fundamental interpretations of the limits and quantitative relationships between their values and compositional factors are more complex. Previous studies examined artificially-prepared soil samples that contained monomineralic clays and a non-clay substance(quartz sand). These studies have shown that in soils without expandable clays the PL and LL water contents were mostly related to surface area and clay content. For soils that contain expandable clays, the PL and LL values are also dependent on interlayer water content. Hence, expandable clay mineral contents are needed to calculate PL and LL values. These relationships have been presented in a general analytical form. The aim of these investigations was to identify practical applications. Mineral compositions and surface areas of five randomly selected natural soil samples were used to estimate PL and LL values. The estimated values were compared to experimentally measured liquid limits (by the ‘fall-cone’ test) and plastic limit (by the ‘rolling thread’ test) values. The measured PL values ranged from 18.77 to 44.92% and the LL values from 31.19 to 82.10%. The differences between estimated and measured Atterberg Limits were 3.0–7.1% for thePL and 2.7–7.8% for the LL. Minor differences in measured and estimated Atterberg Limits were probably due to soil organic matter (1.2–2.7%).
Keywords: ATTERBERG LIMITS; CLAYS; LIQUID LIMIT; PLASTIC LIMIT; SPECIFIC SURFACE OF SOILS